2023
DOI: 10.1186/s12964-022-01023-x
|View full text |Cite
|
Sign up to set email alerts
|

Lower SLC7A2 expression is associated with enhanced multidrug resistance, less immune infiltrates and worse prognosis of NSCLC

Abstract: Background Solute carrier family 7 member 2 (SLC7A2), a cationic amino acid transporter, is lowly expressed in ovarian and hepatocellular cancers, which is associated with their worse prognosis. However, its roles in the prognosis, drug resistance and immune infiltration in non-small-cell lung cancer (NSCLC) are unclear. Methods We chose SLC7A2 from RNA-Seq of paclitaxel/cisplatin-resistant A549 cells, then bioinformatics, cell lines construction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…When overexpressed, it behaved like a tumor suppressor, especially in low-growth ER-positive subtypes [ 6 ]. Jiang et al found that SLC7A2 increased drug sensitivity, immune infiltration, and survival in NSCLC [ 12 ]. The upregulation of SLC7A7 increased the levels of arginine in tumor cells, thus promoting their migration and invasion [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When overexpressed, it behaved like a tumor suppressor, especially in low-growth ER-positive subtypes [ 6 ]. Jiang et al found that SLC7A2 increased drug sensitivity, immune infiltration, and survival in NSCLC [ 12 ]. The upregulation of SLC7A7 increased the levels of arginine in tumor cells, thus promoting their migration and invasion [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified some genes associated with cancer progression. SLC7 genes were reported to be correlated with the prognosis of lung cancer [11][12][13][14]. SLC7A5 was overexpressed in LUAD and significantly correlated with the Ki-67 labeling index, which can increase metabolic activity and is associated with tumor cell growth [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that AMPK augments SLC7A2 expression to increase the sensitivity of cancer cells to anti-cancer drugs. More importantly, SLC7A2 modulates immune infiltration and correlates to the infiltrated neutrophils, macrophages, dendritic cells, and their markers such as CD86, HLA-DPA1, and ITGAM [ 93 ]. The protecting role of SLC7A2 from colitis-associated carcinogenesis in the setting of chronic colitis was proved in a study.…”
Section: Slcs In Cancermentioning
confidence: 99%